(untitled) (Sains Humanika, 2025)
Financial stress is a significant predictor on job performance and the need for managing financial stress has become the main focus of every employee in all organization. This study identifies the effect of financial stress on job performance among supporting employees in the manufacturing sector in the state of Johor. The sample was selected using the convenience sampling method and a total of 214 support workers from four construction companies were involved in this study. The quantitative data was collected through self-administered questionnaire to measure all the variables and the data was analyzed by using descriptive and inferential statistical methods. The research findings shows that there was a weak positive influence of financial stress on job performance. This study also found that perceived organizational support acted as a significant moderator in weakening the relationship between financial stress and work performance. In this respect, employees who perceived high organizational support are more likely than are employees who perceived low organizational support to be able to reduce the potential effects of financial stress on job performance. The results of this study clarify knowledge regarding the financial stress and thus, potentially improves and enhance the stress management practices among employees.